Gut bacteria of adult and larval Cotinis nitida Linnaeus (Coleoptera: Scarabaeidae) demonstrate community differences according to respective life stage and gut region - Kucuk, Roy A.; Campbell, Barbara J.; Lyon, Nicholas J.; Shelby, Emily A.; Caterino, Michael S. (Frontiers in Microbiology, 2023)
The close association between bacteria and insect hosts has played an indispensable role in insect diversity and ecology. Thus, continued characterization of such insect-associatedmicrobial communities is imperative, especially those of saprophagous scarab beetles. The bacterial community of the digestive tract of adults and larvae of the cetoniine scarab species Cotinis nitida is characterized according to life stage, gut structure, and sex via high-throughput 16S rRNA gene amplicon sequencing. Through permutational ANOVAs of the resulting sequences, bacterial communities of the digestive system are shown to differ significantly between adults and larvae in taxon richness, evenness and relatedness. Significant bacterial community-level differences are also observed between the midgut and hindgut in adult beetles, while no significant host-sex differences are observed. The partitioning between bacterial 2 communities in the larval digestive system is shown through significant differences in two distinct hindgut regions, the ileum and the expanded paunch, but not between the midgut and ileum portion of the hindgut region. These data further corroborate the hypothesis of strong community partitioning in the gut of members of the Scarabaeoidea, suggest hypotheses of physiological-digestive association, and also demonstrate the presence of a seemingly unusual non-scarab-associated taxon. These findings contribute to a general portrait of scarabaeoid digestive tract bacterial communities while illuminating the microbiome of a common new world cetoniine of the Gymnetini-a tribe largely neglected in scarab and beetle microbiome and symbiosis literature.